PEDAGOGICAL EDUCATION SYSTEM IN ISLAM - Rakhimov Fayzullo; Imam Termizi (Galaxy International Interdisciplinary Research Journal, 2021)
The article is devoted to the study of the basic principles of the Islamic pedagogical system in the history of the development of Islamic education in Uzbekistan and at the present stage. The Muslim model of education was based primarily on the Qur’an and Sunnah, as well as on the scientific and theoretical achievements of early Muslim thinkers